The Neoplatonic Socrates - Tarrant, Harold; Layne, Danielle A. (Book collections on Project MUSE., 2014)
The Neoplatonic Socrates explores the portrait of the great philosopher as developed by the Platonists in the first six centuries C.E. and examines Neoplatonic attitudes toward themes relevant to the contemporary studies of Socrates.